Assessing the European Union's global climate change leadership: from Copenhagen to the Paris Agreement. Issue 2 (23rd February 2017) - Parker, Charles F.; Karlsson, Christer; Hjerpe, Mattias
Abstract: This contribution examines the role European Union (EU) leadership played in the outcome of the 2015 COP21 climate summit in Paris. The EU's attempts to realise its bid for climate change leadership are scrutinised by investigating to what extent the EU is actually recognised as a leader by potential followers and to what extent the EU has succeeded in achieving its negotiation objectives. To address these issues we utilize survey data collected at eight UN climate summits from 2008 to 2015 and evaluate the results of the climate negotiations particularly with respect to the Union's goal attainment in Copenhagen and Paris. Our findings, which reveal a fragmented leadership landscape in which the EU must adjust its leadership strategies in relation to other powerful actors, such as the United States and China, provide insights into leadership theory and the EU's prospects for exerting influence as an external actor on the world stage.